Neuroprotective Effects of Fluoxetine Against Chronic Stress-Induced Neural Inflammation and Apoptosis: Involvement of the p38 Activity - Zhao, Yuxiao; Shang, Pan; Wang, Meijian; Xie, Min; Liu, Jian (Frontiers in Physiology, 2020)
Depression is considered a widespread neuropsychiatric disease associated with neuronal injury within specific brain regions. Fluoxetine, a selective serotonin reuptake inhibitor, has been widely used in depressed patients. Recently, fluoxetine was demonstrated neuroprotective effects apart from the effect on serotonin. However, the underlying mechanism involved in this neuroprotection remains unclear, in particular whether fluoxetine exerts antidepressant effects via protecting against neuronal injury. Here we found that treatment with fluoxetine (10 mg/kg, i.p.) for two weeks ameliorated depression-like behaviors in a chronic unpredictable mild stress (CUMS)-induced rat model of depression, and was accompanied with an alleviation of glia activation and inhibition of interleukin-1β (IL-1β), interferon gamma (IFN-γ) and tumor necrosis factor-a (TNF-a) expression in the hippocampal dentate gyrus (DG) region. Meanwhile, CUMS rats treated with fluoxetine showed reductions in neuronal apoptosis and a downregulation of the apoptotic protein Bax, cleaved caspase 3 and caspase 9 levels. These effects appear to involve a downregulation of p38 mitogen-activated protein kinase (MAPK) signaling within the DG hippocampus as the specific inhibitor of p38 MAPK, SB203580, significantly suppressed apoptosis, as well as ameliorated depressive behaviors resulting from CUMS exposure. Moreover, fluoxetine could rescue neuronal deterioration and depression-like phenotypes caused by overexpression of p38 in DG. This finding extends our knowledge on the antidepressant-like effects of fluoxetine, which appear to at least partially profit from neuroprotection against inflammation and neuronal apoptosis via downregulation of the p38 MAPK pathway. The neuroprotective mechanisms of fluoxetine may provide for some novel therapeutic avenues for stress-related neurological diseases.